A retrospective cohort study on the protective effect of influenza vaccination during pregnancy in Gansu Province - Xue-Feng Liang; Juan-Xia Peng; Di Sun; Bing-Ling Zhang; Jing An; Xiao-Shu Zhang (Taylor & Francis Group, 2024)
To evaluate the Vaccine Effectiveness (VE) of the Influenza Vaccine (InfV) during pregnancy in Gansu province. A retrospective cohort of pregnant women vaccinated with InfV was constructed using the electronic case system and immunization planning system of Gansu province. Outcome information of Influenza-Like Illness (ILI) in pregnant women after vaccination with InfV during the influenza epidemic seasons from 2019 to 2021 was collected. The log-binomial model was used to estimate the adjusted Risk Ratio (RR), VE, and their Confidence Intervals (CI). The incidence rates of the InfV vaccination group and the non-vaccination group during pregnancy in Gansu province were 4.70% (54/1,150) and 6.91% (16,990/245,754), respectively. The adjusted RR was 0.78 (95%CI 0.43-0.75), and the adjusted VE was 22.20 (95%CI 0.79-40.30). Vaccination with InfV during pregnancy in Gansu province from 2019 to 2021 has a protective effect against ILI in pregnant women, and there is no difference in vaccination at different stages of pregnancy.